2009
DOI: 10.1007/s10384-008-0627-6
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral cataract surgery: A controlled clinical trial

Abstract: Simultaneous bilateral cataract surgery may be an effective and safe bilateral cataract surgery option with a high degree of patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 21 publications
3
42
1
Order By: Relevance
“…The present multicenter randomized clinical trial tackled the assessment of safety and effectiveness of ISBCS versus conventional DSBCS with a larger sample and a longer follow-up than in previous randomized trials. 15,17 We did not observe any cases of endophthalmitis, a result consistent with findings in 2 smaller randomized clinical trials, 15,17 1 nonrandomized clinical trial, 23 and several case series. [3][4][5][6][7][8][9][10][11] However, the range of the incidence of endophthalmitis reported after 10 in whom no cases of endophthalmitis were observed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present multicenter randomized clinical trial tackled the assessment of safety and effectiveness of ISBCS versus conventional DSBCS with a larger sample and a longer follow-up than in previous randomized trials. 15,17 We did not observe any cases of endophthalmitis, a result consistent with findings in 2 smaller randomized clinical trials, 15,17 1 nonrandomized clinical trial, 23 and several case series. [3][4][5][6][7][8][9][10][11] However, the range of the incidence of endophthalmitis reported after 10 in whom no cases of endophthalmitis were observed.…”
Section: Discussionsupporting
confidence: 90%
“…Although that study did not use safety information as the main outcome variable to estimate sample size requirements, the data reported showed no statistically significant differences in intraoperative or postoperative complications between patients assigned to ISBCS and patients assigned to DSBCS. 15 Even though these studies were underpowered to report on safety issues with scientific certainty, no cases of unilateral or bilateral endophthalmitis were observed, supporting previous findings in several case series 3-11 and some comparative prospective nonrandomized studies, 23 all of which reported extensively on the absence of relevant complications. The present multicenter randomized clinical trial tackled the assessment of safety and effectiveness of ISBCS versus conventional DSBCS with a larger sample and a longer follow-up than in previous randomized trials.…”
Section: Discussionsupporting
confidence: 71%
“…[4][5][6][7][8][9][10][11][12] In addition, patient-rated satisfaction was excellent in both the study group and the control group. 2 The economic part of the study confirms the hypothesis that simultaneous bilateral cataract surgery provides meaningful savings in both the health-care and non-health-care costs.…”
Section: Discussionmentioning
confidence: 84%
“…Collectively, the literature for immediate sequential bilateral phacoemulsification is reassuring with respect to the low risk for endophthalmitis when well-designed aseptic protocols have been followed. [36][37][38][39][40][41][42][43][44] In most of these studies, the second eye is treated as though it were from a new patient, with separate draping, gowns, gloves, instrumentation, medications, and disposable supplies. Nevertheless, anecdotal cases of bilateral endophthalmitis have been reported, and the true risk is difficult to ascertain.…”
Section: Risk Factorsmentioning
confidence: 99%